Strategic Management of Madrasah Principals in Enhancing The Quality of Islamic Education - Siagian, Zainidah; Akhir, Muhammad; Iqbal, Muhammad; Ependi, Rustam (Hikmah, 2025)
The quality of Islamic education in madrasahs still faces challenges such as low teacher discipline, suboptimal infrastructure, and minimal community involvement. This study aims to analyze the strategies of madrasah principals in developing the quality of Islamic education through strategic planning, teacher competency development, and parent and community involvement. Using a qualitative approach with a case study method, data was collected through interviews, observations, and documentation. The results of the study indicate that quality planning is carried out through annual meetings with the foundation, teachers, and staff, and then implemented through the ERKAM application. To improve teacher competencies, the madrasah principal conducts supervision, motivation, and training guidance, although some teachers are still found to be undisciplined. Facility development is carried out through planning, utilization, and maintenance, but some facilities are still incomplete. Community relations are quite good, as indicated by participation in madrasah activities. Parent involvement also supports the achievement of educational quality. The implications of this study emphasize the importance of participatory and quality-oriented leadership in promoting the overall progress of madrasahs.